Aplikasi Sistem Pakar Diagnosa Penyakit Virus Corona Dengan Metode Certainty Factor dan Forward Chaining Berbasis Web - Lurita Sinta Siregar (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The case of the corona virus appeared and attacked humans for the first time in Wuhan Province, China. Covid- 19 was first reported in Indonesia on March 2, 2020, with 2 cases. Since the WHO declared the status of the COVID-19 outbreak to be a global pandemic, the number of positive confirmed cases, recovered, and death cases has been increasing day by day. In the expert system there is a classification of diagnoses, methods that can be used for diagnosis, one of which is the Certainty Factor (CF) method. It can be said that with the design of an expert system application in diagnosing Covid- 19 disease using the web-based Certainty Factor method, the system can be used by the public to find out from the beginning the diagnosis of Covid-19 disease. This is because of the application of the methods that are included in the coding of the program so that this system can help the community and the hospital.